Pengaruh Brand Image, Brand Trust, Dan Kualitas Informasi Terhadap Keputusan Pembelian Di Shopee ( Studi Kasus Pada Mahasiswa Angkatan 2018 FEB Universitas Islam Malang ) - Alhidayatullah Nur Utomo Putra; Nurhajati Nurhajati; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract Rapid technological developments affect the development of e-commerce, including the behavior of consumer purchasing decisions. The development of online shopping services in Indonesia is very fast. Currently, there are various marketplace platforms such as Tokopedia, Shopee, Lazada and others. Based on information stating that the Shopee marketplace won the Top Marketpalce award in Indonesia. The survey results show that Shopee is the marketplace with the highest number of visitors in Indonesia in the second quarter of 2020 with 93,440,300 monthly web visitors compared to Tokopedia, Lazada, Bukalapak, etc. In this study, the formulation of the problem is how brand image, brand trust and information quality affect purchasing decisions at shope. The purpose of this study was to determine and analyze the effect of brand image, brand trust and quality of information on purchasing decisions at shope. This study uses quantitative methods. The data source in this study used a purposive sampling technique where the criteria in this study were FEB Unisma students who had made purchases at shope. Based on the research that has been done, it can be concluded that Brand Image, Brand Trust and Information Quality have a significant effect on purchasing decisions. The higher the brand image, brand trust and quality of information, the higher the purchase decision. Keywords: Brand Image, Brand Trust, Quality Of Information And Purchasing Decisions